Development of Basic Physics Experiment Textbooks Based on Pictorial Riddles - Apriani Sijabat; Herna Febrianty Sianipar; Osco P. Sijabat; Theresia Monika Siahaan; Christa Voni Roulina Sinaga (Lensa: Jurnal Kependidikan Fisika, 2021)
Basic physics experiment textbooks are widely used by lecturers and students in physics courses at universities, but relevant and easy-to-use basic physics experiment textbooks are not yet available. Most of the available books are practical books. The purpose of this study was to determine the stages of developing a basic physics experimental textbook based on pictorial riddles. This type of research is research and development (R&D) research. The research uses the Plomp Model with three stages, namely preliminary research, prototype or development, and assessment. The subjects of this study were students of the Physics Education study program at the University of HKBP Nommensen Pematangsiantar. Data analysis used descriptive quantitative. The results showed that the development value of pictorial riddle-based textbooks had a high level of attractiveness based on the assessment of material/content experts reaching 93.75%. The development value based on pictorial riddle has a high level of attractiveness based on field test assessments reaching 91%. This shows that the development of pictorial riddle-based basic physics experimental textbooks has good quality and is suitable for use to improve student learning outcomes in basic physics experimental subjects.